2006
DOI: 10.1007/s00595-006-3266-x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features of Human Papilloma Virus 16 and Its Association with the Development and Progression of Anal Squamous Cell Carcinoma

Abstract: These findings show that HPV16 infection is closely involved in the development of anal SCC and suggest that the change in the genome occurs at the stage of microinvasive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Case series of invasive lesions have been included in Table 2.17 (available at http://monographs. iarc.fr/ENG/Monographs/vol100B/100B-06-Table2 .17.pd f ) (Kagawa et al, 2006;Varnai et al, 2006;Laytragoon-Lewin et al, 2007;Tachezy et al, 2007). All studies found high proportions of HPV in the tumours, predominantly HPV 16.…”
Section: (A) Case Seriesmentioning
confidence: 98%
“…Case series of invasive lesions have been included in Table 2.17 (available at http://monographs. iarc.fr/ENG/Monographs/vol100B/100B-06-Table2 .17.pd f ) (Kagawa et al, 2006;Varnai et al, 2006;Laytragoon-Lewin et al, 2007;Tachezy et al, 2007). All studies found high proportions of HPV in the tumours, predominantly HPV 16.…”
Section: (A) Case Seriesmentioning
confidence: 98%
“…Detection of HPV DNA was performed by polymerase chain reaction (PCR) using SPF primers, 12 which amplify a fragment of 75 base pairs of the viral genome and developed to promote sensitive amplification of the most clinically relevant HPV genotypes. The assay is capable of detecting the genotypes currently known as high risk HPVs (16,18,26,31,33,35,39,45,51,52,53,56,58,59,66,68, 73 e 82), as well as low-risk HPV genotypes (6,11,40,43,44,54,70) and some additional types.…”
Section: Detection Of Hpv Genome In Tumor Samplesmentioning
confidence: 99%
“…Infection with oncogenic, or high-risk, HPV-16 was detected in all cases. Other studies also report that HPV-16 was the main HPV type found in over 80% of carcinomas [10,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%